Alkaline pretreatment and enzymatic hydrolysis of corn stover for bioethanol production (Research, Society and Development, 2021)
The demand for ethanol in Brazil is growing. However, although the country is one of the largest producers of this fuel, it is still necessary to diversify the production matrix. In that regard, studies with different raw materials are needed, mainly the use of low cost and high available wastes such as lignocellulosic residues from agriculture. Therefore, this study aimed to analyze the bioethanol production from corn stover. An alkaline pretreatment (CaO) was carried out, followed by enzymatic hydrolysis (Cellic Ctec2 and Cellic Htec2) to obtain fermentable sugars. The best experimental condition for the pretreatment and hydrolysis steps resulted in a solution with 0.31 gsugar∙gbiomass-1. Then, the fermentation was performed by the industrial strain of Saccharomyces cerevisiae (PE-2) and by the wild yeast strain Wickerhamomyces sp. (UFFS-CE-3.1.2). The yield obtained was 0.38 gethanol∙gdry biomass-1 was, demonstrating the potential of this process for bioethanol production.